Beyond crisis: Enacted sense-making among ethnic minority carers of people with dementia in Australia. (August 2021) - Brijnath, Bianca; Gilbert, Andrew Simon; Kent, Mike; Ellis, Katie; Browning, Colette; Goeman, Dianne; Adams, Jon; Antoniades, Josefine
The 'family crisis' narrative is frequently used in dementia studies to explain ethnic minority families' pathways to health and aged care and why there is delayed dementia diagnoses in ethnic minority communities. Such narratives may obscure the family carers' agency in negotiating services and managing personal, social and structural burdens in the lead up to diagnosis. To illuminate agency, this article describes ethnic minority families' pathways to a dementia diagnosis using the concept of sense-making. Three case studies were drawn from 56 video interviews with family carers of older adults with dementia from Chinese, Arab and Indian backgrounds. Interviews were conducted across Australia from February to August 2018, then translated, transcribed and thematically analysed. Findings suggest families did not enter into formal care because of a crisis, instead navigating fragmented systems and conflicting advice to obtain a dementia diagnosis and access to relevant care. This experience was driven by sense-making (a search for plausible explanations) that involved family carers interpreting discrepant cues in changes to the behaviour of the person with dementia over time, managing conflicting (medical) advice about these discrepancies and reinterpreting their relationships with hindsight. The sense-making concept offers a more constructive hermeneutic than the 'family crisis' narrative as it illuminates the agency of carers' in understanding changed behaviours, negotiating services and managing personal, social and structural barriers pre-diagnosis. The concept also demonstrates the need for a multimodal approach to promoting timely diagnosis of dementia in ethnic minority communities through dementia awareness and literacy campaigns as well as initiatives that address structural inequities.